Impact of Government Debt on Economic Growth in Kenya: A Critical Literature Review - Murungi, Silveria Mukwandiga; Okiro, Kennedy (European Scientific Journal, ESJ, 2018)
The study examined the impact of government debt on economic growth through extensive review of relevant theoretical and empirical literature. Governments borrow to cover budget deficits. The debt is obtained either from the domestic market or from external sources. Government debt by Greece proved to be bad for the economy while government debt by USA which has the highest debt in the world proved to be manageable. This led to the need to examine the impact of government debt on economic growth in Kenya. The major theories examined included Adolph Wagner’s law of increasing state activity, the debt overhang theory, crowding out theory and the Ricardian equivalence theory. The main objective of the critical literature review was to review the literature done on the impact of government debt on economic growth while the specific objectives were to examine the impact of government debt on economic growth, to investigate the effects of macroeconomic variables on the relationship between government debt and economic growth, to establish the effects of regulatory reforms on the relationship between government debt and economic growth, and to review the joint effect of macroeconomic variables and regulatory reforms on government debt and economic growth. The majority of the findings from the literature reviewed on government debt indicated that there was an impact of government debt on economic growth; some showed a positive economic growth while others showed a negative economic growth.